Subtansiasi Nilai-Nilai Jiwa dalam Pendidikan Islam: Perspektif Ibnā - Prasetia, Senata Adi (MUSLIM HERITAGE, 2023)
AbstractThis article critically explores how to substantiate the values of the soul in Islamic education using Ibn Sinā's perspective. As a discourse that interests Muslim scholars, the concept of the soul has experienced ups and downs and passed through various endless debates. Ibn Sinā as one of the Muslim philosophers concerned with the soul managed to develop a good conception of the soul that received extraordinary attention and appreciation from Muslim philosophers after him, such as al-Ghazāli, Fakhruddin al-Rāzi, Ibn Rushd, and Western scholars. Using an exploratory, descriptive, and analytical approach, this article argues that the soul is a spiritual substance that inspires the body so that it lives, which then becomes a tool for acquiring knowledge and divine (theological) knowledge. The practice of teaching Islamic education, thus, cannot be separated from the touch of Ibn Sinā's soul element. For Sinā, Islamic education must reconsider psychological aspects to develop students' potential naturally to become perfect human beings (insan kamil). AbstrakArtikel ini, secara kritis, mengeksplorasi bagaimana substansiasi nilai kejiwaan dalam Pendidikan Islam menggunakan perspektif Ibn Sinā. Sebagai suatu diskursus yang menyita atensi ilmuwan Muslim, konsep kejiwaan berkembang sedemikian rupa serta membuka ruang dialektika yang beragam. Ibn Sinā, satu dari sekian filsuf Muslim yang concern terhadap kejiwaan, telah berhasil mengembangkan konsepsi kejiwaan dengan sangat baik sehingga mendapat atensi dan apresiasi yang luar biasa dari kalangan filsuf muslim setelahnya, seperti al-Ghazāli, Fakhruddin al-Rāzi, Ibn Rushd, dan sarjana Barat. Dengan menggunakan pendekatan eksploratif, deskriptis, dan analitis, artikel ini berpendapat jiwa merupakan substansi ruhani yang mengilhami jasad sehingga ia hidup dan menjadi piranti untuk memperoleh ilmu dan pengetahuan ketuhanan (teologis). Praktik pendidikan Islam, dalam hal ini, tidak terlepas dari sentuhan unsur kejiwaan Ibn Sinā. Bagi Sinā, pendidikan Islam harus merekonsiderasi aspek-aspek kejiwaan guna pengembangan potensi peserta didik secara fitri sehingga mampu meraih derajat manusia sempurna (insan kamil).